Analisis Kebutuhan Ground Support Equipment (Gse) Training Approve Sebagai Upaya Terhadap Peningkatan Kompetensi Operator di PT. GMF Aeroasia - Zusnita Muizu, Wa Ode; Putri, Annisa Dewinta (STIE Mahardhika, 2018)
This research had been conducted in PT. GMF AeroAsia. The aim of this study is to determine analysis process image of GSE (Ground Support Equipment) Training Approve so that it can improve GSE operator competency at PT. GMF AeroAsia. The method used in this research is description method. The data collection techniques by the author were making observation, interviews, and literature study. The results from these studies shows that GSE Training Approve is needed to fill GSE operator competency gap with syllabus and curriculum issued to be a competent GSE operator. GSE Training Approve is not currently being implemented due to some administrative and substance requirements that are still being processed for the issuance of its training certification. Suggestion for this training is that it needs to have a clear and appropriate curriculum based on teaching competence and prepare completeness of the requirements so that the certificate will be issued.